The exclusion of the black subject and the negation of race in the academic production in International Relations in Brazil - Ananda Vilela da Silva Oliveira (Monções, 2019)
A political system forged in the logic of whiteness and Brazilian racism imposes classifications of superiority and inferiority in social hierarchies. As such, black subjects, defined from racist scientific discourses, are irrational and unintelligent, while white subjects reap the privileges acquired through the improper exploitation of enslaved labor. To think about the discipline of International Relations in Brazil is to understand that this context of exploitation, appropriation and extermination of the black population in the country permeates debates about the international in this field of knowledge, even if silenced through the mechanisms of exclusion of knowledge production in science. Modern. Under this umbrella, this article seeks to understand how the category race and racial context in Brazil cross the construction of the IR field in the country. In order to expand the historiographical debates about the institutionalization of postgraduate courses in IR in Brazil, a decolonial approach in afrodiasporic perspective is used. To this end, a bibliographic survey on IR in the country is undertaken, tangential categories such as coloniality, racism and epistemicide as analytical tools that enable the reading of the coloniality of knowledge in the teaching and research of IR.